Acid Dissociation Constant (pKa) of Common Monoethylene Glycol (MEG) Regeneration Organic Acids and Methyldiethanolamine at Varying MEG Concentration, Temperature, and Ionic Strength - Soames, A.; Iglauer, Stefan; Barifcani, Ahmed; Gubner, Rolf (American Chemical Society, 2018)
© 2018 American Chemical Society. The acid dissociation constants (pKa) of four organic acids (formic, acetic, propanoic, and butanoic) commonly found in monoethylene glycol (MEG) regeneration systems and methyldiethanolamine (MDEA) were measured via potentiometric titration. Dissociation constants were measured within varying concentration of MEG solution (0, 30, 40, 50, 60, 70, and 80 wt %) and at varying temperature (25, 30, 40, 50, 60, 70, and 80 °C). Thermodynamic properties of the dissociation process including Gibbs free energy (?G° kJ mol-1), standard enthalpy (?H° kJ mol-1), and entropy (?S° kJ mol-1K-1) were calculated at 25 °C using the van't Hoff equation. Comparison of the reported experimental pKavalues and calculated thermodynamic properties in aqueous solution to the literature demonstrated good agreement. Two models have been proposed to calculate the pKaof acetic acid and MDEA within MEG solutions of varying concentration, temperature, and ionic strength. The proposed models have an average error of 0.413% and 0.265% for acetic acid and MDEA, respectively.